2017
DOI: 10.1002/jccs.201700049
|View full text |Cite
|
Sign up to set email alerts
|

UV Spectrum of the Simplest Deuterated Criegee Intermediate CD2OO

Abstract: The ultraviolet (UV) absorption spectrum of the simplest deuterated Criegee intermediate CD2OO has been measured and compared with that of CH2OO. While the UV spectra of CH2OO and CD2OO are similar in the overall shape, distinctive oscillatory structures at the long wavelength side of the absorption band show clear effect of isotopic substitution. The average spacing between the vibrational peaks decreases from 606 cm−1 for CH2OO to 528 cm−1 for CD2OO. This large isotope effect cannot be explained by one‐dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Photodissociation of CH 2 OO from this excitation is reported to proceed with a quantum yield of unity (e.g. Ting et al, 2014), producing HCHO and either O( 3 P) or O( 1 D). Production of O( 1 D) has been reported to be dominant (e.g.…”
Section: Structure and Spectroscopy Of Criegee Intermediatesmentioning
confidence: 99%
“…Photodissociation of CH 2 OO from this excitation is reported to proceed with a quantum yield of unity (e.g. Ting et al, 2014), producing HCHO and either O( 3 P) or O( 1 D). Production of O( 1 D) has been reported to be dominant (e.g.…”
Section: Structure and Spectroscopy Of Criegee Intermediatesmentioning
confidence: 99%
“…44 Recently, Ting and Lin have reported the absorption spectrum of the deuterated Criegee intermediate, CD2OO, finding significant isotope shifts. 84 Calculations suggest that CH2OO maintains its planar structure following excitation to the B̃1A′ state, with the major geometric changes being contraction of the CO bond, extension of the OO bond and a decrease in the COO bond angle. 85,86 However, projections of the ground state vibrational wavefunctions, calculated at the MR-PT2 level, onto the B̃ state surface, suggested that three modes comprising the out-of-plane CH2 wag, CH2…”
Section: Clchoo Absorption Spectrummentioning
confidence: 99%
“…Despite this, the photophysics and photochemistry of CIs have received surprisingly little attention when compared to their ground-state reactivities. The electronic absorption spectra of the small CIs (≤C 4 ) have formed the basis of some experimental , and theoretical studies, and it is now understood that the absorption spectra of CIs are dominated by strongly absorbing ππ* states, local to the carbonyl oxide moiety. ,, The spectra of CH 2 OO and CH 3 CHOO have previously been simulated with elegant techniques that may be difficult to extend to larger CI systems. ,, Additionally, the majority of studies have used a reduced dimensionality approach for generating the initial starting geometries. Notably, Sršeň et al have shown that the computationally demanding high-order CC2/3, ADC(3), and EOM-CCSD/T methods perform well and reproduce the electronic absorption spectra of CH 2 OO and CH 3 CHOO, but these methods are restrictive for larger CIs.…”
Section: Introductionmentioning
confidence: 99%